Analysis of Actors and Discourse in the Amendment of Ontario’s Regulated Health Professions Act, 1991, to Support Interprofessional Collaboration - Kapral, Olena (Université d'Ottawa / University of Ottawa, 2013)
Identifying how policy proposals are selected by policy-makers is an important question for scholars. This thesis evaluates the use of discourse and the role of actors in the exchange of ideas to support interprofessional collaboration (IPC) among Ontario’s regulatory colleges. A variation of discourse analysis was developed, based on the seven areas of reality that are constructed by language, to evaluate the interactions between state and policy actors. I argue that actors did not appear to engage in meaningful discourse because the state established the parameters of the consultative processes, which suggests the expert consultative processes were tools to legitimize the policy process for Bill 179. The state appears to have increasingly greater control of both the content and context of policy- making in this field. Further evaluation of the interactions between health professional organizations and the state is needed to better understand the importance of discourse in the health policy process.
Keywords: Actors; Discourse; Policy Process; Regulated Health Professions; Ontario